Competitiveness and Industrial Policy: From Rationalities of Failure Towards the Ability to Evolve - Michael Peneder (Austrian Institute of Economic Research (WIFO), 2016)
This paper elaborates a dynamic rationale of industrial policy, focusing on how to strengthen the socio-economic system's ability to evolve, i.e., how to achieve high real income together with qualitative change. It highlights that the ubiquitous rationalities of failure, be it of markets, governments, or systems, are rooted in a peculiar habit of accepting hypothetical perfect states as normative benchmarks. In contrast, a dynamic logic of intervention should start from the question, what the system aims to accomplish. Combining the structuralist ontology of micro, meso and macro with the functional principles of evolutionary change, the paper proposes a general typology of economic policies based on their respective contributions to the system's ability to evolve.
Keywords: 330; Industrial policy; competitiveness; evolutionary economics; structural change